The role of warehouse in e-business - Pavlov, Nikola; Đurđević, Dragan; Božić, Mladen (E-business technologies conference proceedings, 2021)
The expansion of the application in modern information technologies has significantly contributed to the intensification of electronic business in all areas of modern life. Nowadays, the terms e-payment, e-commerce, e-scheduling, etc. are increasingly applied. E-business is based on the use of the internet in connecting companies with their suppliers, warehouses, customers, and other entities. The basic application of solutions based on e-business involves the integration and coordination of information, goods, and energy flows, including the implementation of new business models. Observed in this new context, the warehouse as an essential component of supply chains faces new challenges. Therefore, the main goal of this paper is to review/redefine the role of the warehouse in e-business. Some forms of e-business and their impact on the warehouse are especially explained. For the identified requirements, which e-business makes towards the warehouse, corresponding concepts/solutions of such warehouses applied in practice have been analyzed.